Audio universe: tour of the solar system. Issue 2 (1st April 2022) - Harrison, Chris; Trayford, James; Harrison, Leigh; Bonne, Nicolas
Abstract : Chris Harrison, James Trayford, Leigh Harrison and Nicolas Bonne have developed a sensory odyssey to demonstrate how the Universe can be made more accessible. Abstract: Chris Harrison, James Trayford, Leigh Harrison and Nicolas Bonne have developed a sensory odyssey to demonstrate how the Universe can be made more accessible.